Immunomodulatory effects of Bacillus subtilis-fermented soybean extract in mice. Issue 4 (2nd October 2022) - Ali, Sekendar; Birhanu, Biruk Tesfaye; Lee, Eon-Bee; Quah, Yixian; Boby, Naila; Suk, Kyoungho; Lee, Sam-Pin; Lee, Seung-Jin; Park, Seung-Chun
ABSTRACT: This study investigated the potential immunomodulatory effects of fermented soybean extract (FSE) in RAW264.7 cells and BALB/c mice. The expression of proinflammatory cytokines in RAW264.7 cells was measured after LPS stimulation in the presence or absence of FSE. Mice were orally administered 125, 250, and 500 mg/kg FSE for 21 days, and their immune response was analyzed. In RAW264.7 cells, FSE significantly reduced the expression of proinflammatory cytokines. In vivo experiments revealed significantly elevated splenocyte proliferation; neutrophil migration; phagocytic activities; expression of CD18 +, CD4 +, and CD8 + T cells; and expression of IL-2, IL-4, and IFN-γ. The major compounds in FSE were identified by GC–MS and by LC–MS/MS. Molecular docking analysis showed that daidzin, genistin and daidzein could potentially bind to the human high-affinity FcγRI–IgG complex to be involved in immunological responses. Taken together, FSE can be a candidate ingredient for health functional food with enhanced immunomodulating ability.